Lavoro subordinato e lavoro autonomo, oggi - Massimo Roccella (Quaderni di Sociologia, 2008)
The determination of an individual’s employment status is a troublesome question. Aim of this essay is to draw a clearer distinction between employees and self-employed.An increasing development of ‘atypical’ self-employment (ie people held to be self-employed, when the reality is that they are economically dependent workers: ‘semi-subordinate’ workers or quasi-employees, ‘employer-co-ordinated’ freelance workers) has brought about a number of proposals, suggesting either to extend parts of the protective regulations applicable to employees to this category of workers, or to establish a new set of protection measures covering all people working for another person, not just those employed under a contract of employment. All these proposals are called into question by the author.Basing on the case of call-center workers, he also questions the usefulness of the criteria most taken into account by the courts in order to determine whether a person is employed as an employee: ‘heterodirection’, ie the degree of control exercised by the employer over the employee, and the absence of discretion over the working schedule on the part of the worker.In the last part of his essay, the author proposes a different approach to the traditional notion of dependent employment, setting a great value on the Italian Constitutional Court’s jurisprudence according to which the worker’s subordination in a strict sense is characterized by something more specific than ‘heterodirection’ or economic dependence: what the Constitutional Court (and the author) underlines is that employees are in a condition of ‘double non-ownership’, since they have no control both over the production organization and the value of what they produce.Therefore, if really non-genuine self-employed should be subsumed under the category of dependent employment, economically weak self-employment could be granted a certain level of social protection (eg social security benefits, such as schemes covering old-age benefits, child allowances and costs of long-term nursing, disability, illness, risk of losses of income), but it should be nevertheless considered as self-employment.